Some comparisons of the Lepidopterous wings - House, Edouard W. (My University, 1902)
Introduction: When the students of the agricultural, domestic and general science courses reach the spring term of their second year, they are required to take up a very interesting subject, that of entomology or the study of insects. Beginning about the first of May and up to the last week in the term you can see students with bug nets in one hand, cyanide bottle in the other, sometimes in twos, sometimes threes and sometimes whole squads; such class of people can be seen at all items, morning, noon and night, and in all places after this bug, that moth or butterfly, in fact nearly everything that has six legs and four wings suffers for a short time the ravages of “bug catchers”. Among the numerous organisms that have six legs and four wings, probably the most admired, most attractive, and most sought after are the ones belonging to the order Lepidoptera which includes the butterflies and moths. These are the most attractive to the little children, student collectors, and advanced entomologists.
Citation: House, Edouard W. Some comparisons of the Lepidopterous wings. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Lepidoptera; Entomology; Insect Wings; Theses; Manuscripts (documents)